INFLUENCE OF BILATERAL TRADE WITH CHINA ON PERU’S ECONOMIC GROWTH (2004-2023) - Cachay Huerta, Yajaira Luzmila (2025)
Objective: To determine the degree of influence that bilateral trade with China has had on Peru’s economic growth (2004–2023). Method: The research adopts a retrospective approach with a longitudinal cut, employing a quantitative, non- experimental, and correlational-descriptive design. Historical data were collected on Peru’s GDP, as well as exports and imports with China. For the analysis, an Ordinary Least Squares (OLS) test was conducted using the EViews software. Results: In a joint analysis of exports and imports with Peru’s GDP, it was found that exports had no effect on GDP, whereas imports did have an impact. However, this was clarified through an individual analysis of GDP in relation to each independent variable (exports and imports), which showed that both variables maintain a high degree of correlation. Conclusion: It was confirmed that bilateral trade between Peru and China has been beneficial for the country, as the influence of the Asian giant on Peru’s economic growth is clearly demonstrated through exports and imports.